Mitochondrial DNA copy number is associated with Crohn’s disease: a comprehensive Mendelian randomization analysis - Xianlei Cai; Xueying Li; Chao Liang; Miaozun Zhang; Yuan Xu; Zhebin Dong; Yihui Weng; Weiming Yu (Scientific Reports, 2023)
Abstract Mitochondrial DNA plays a critical role in the pathophysiological process of inflammation. However, the relationship between mitochondrial DNA copy number (mtDNA-CN) and inflammatory bowel diseases (IBD) remains poorly understood. We conducted a comprehensive Mendelian randomization (MR) using three instrumental variables (IVs) to explore the causal associations between mtDNA-CN and IBD, including Crohn's disease (CD), ulcerative colitis (UC). MR-Egger regression, weighted median, inverse-variance weighted (IVW), and weighted mode methods were used to evaluate the potential causal associations. The robustness of the IVW estimates was determined using the leave-one-out sensitivity test. A meta-analysis was conducted to pool the results from the three sets of IVs. Upon analysis, the findings of the current study revealed that genetically predicted mtDNA-CN was not associated with IBD (CD + UC) and UC. The results of MR analyses between mtDNA-CN and CD risk were inconsistent by using three sets of IVs. After a meta-analysis, we found that genetically predicted mtDNA-CN was associated with CD risk (odds ratio = 2.09; 95% confidence interval: 1.37–3.18). This finding was also confirmed by multivariable MR analyses and remained robust when tested with the leave-one-out sensitivity test. In conclusion, genetically predicted mtDNA-CN was found to be associated with CD risk. Therefore, mtDNA levels in the blood could potentially be used as a marker for CD risk assessment. Further studies are needed to elucidate the underlying mechanisms and validate the results of this study.